Pulp, Root Canal and Peri-radicular Conditions: The Need for Re-classification - Abbott, Paul V (Iranian Endodontic Journal, 2024)
Currently no standard, universally accepted, and clinically useful classification of pulp, root canal and peri-radicular conditions is used within the dental profession. Most published classifications are either too simple and miss many of the conditions reported to occur within the pulp, root canal and peri-radicular tissues, or they are too complex for use in clinical settings. Furthermore, many classifications have used inappropriate terminology that has either not been defined or has been poorly defined. The lack of standardisation leads to confusion amongst practitioners and potential uncertainty regarding treatment. It also limits the ability to communicate effectively, to teach appropriately, and to compare data and research findings throughout the world. When developing a classification of tissue conditions or diseases, it is essential that the classification is developed appropriately and meets the recommended criteria for effective clinical, educational and research use. It is also extremely important that correct and well-defined terminology is used since “words do matter”. Popular terminology based on symptoms should be avoided as these have been proven to lead to inappropriate treatment decisions. This review discusses how classifications should be developed for pulp, root canal and peri-radicular conditions. It also discusses the deficiencies of some popular classifications and outlines the classifications that truly address the recommended criteria and reflect the physiological and pathological changes in the pulp, root canal and peri-radicular tissues. Hence, it is recommended that these latter classifications be adopted as the internationally-accepted classifications for future clinical use, as well as for educational, research and communication purposes.